Fundamentals of corporate finance - Brealey, Richard A.
Fundamentals of corporate finance : CD / Richard A. Brealey, Stewart C. Myers, Alan J. Marcus .- Boston : McGraw-Hill/Irwin , 2007 .- 9780073012414 (CD-ROM)